Application of discrete choice experiments to enhance stakeholder engagement as a strategy for advancing implementation: a systematic review. (December 2017) - Salloum, Ramzi; Shenkman, Elizabeth; Louviere, Jordan; Chambers, David
Abstract Background One of the key strategies to successful implementation of effective health-related interventions is targeting improvements in stakeholder engagement. The discrete choice experiment (DCE) is a stated preference technique for eliciting individual preferences over hypothetical alternative scenarios that is increasingly being used in health-related applications. DCEs are a dynamic approach to systematically measure health preferences which can be applied in enhancing stakeholder engagement. However, a knowledge gap exists in characterizing the extent to which DCEs are used in implementation science. Methods We conducted a systematic literature search (up to December 2016) of the English literature to identify and describe the use of DCEs in engaging stakeholders as an implementation strategy. We searched the following electronic databases: MEDLINE, Econlit, PsychINFO, and the CINAHL using mesh terms. Studies were categorized according to application type, stakeholder(s), healthcare setting, and implementation outcome. Results Seventy-five publications were selected for analysis in this systematic review. Studies were categorized by application type: (1) characterizing demand for therapies and treatment technologies (n  = 32), (2) comparing implementation strategies (n  = 22), (3) incentivizing workforce participation (n  = 11), and (4) prioritizing interventions (n  = 10). Stakeholders included providers (n  = 27), patients (n  = 25), caregivers (n  = 5), and administrators (n  = 2). The remaining studies (n  = 16) engaged multiple stakeholders (i.e., combination of patients, caregivers, providers, and/or administrators). The following implementation outcomes were discussed: acceptability (n  = 75), appropriateness (n  = 34), adoption (n  = 19), feasibility (n  = 16), and fidelity (n  = 3). Conclusions The number of DCE studies engaging stakeholders as an implementation strategy has been increasing over the past decade. As DCEs are more widely used as a healthcare assessment tool, there is a wide range of applications for them in stakeholder engagement. The DCE approach could serve as a tool for engaging stakeholders in implementation science.